In vitro and in vivo effects of Puntius javanicus cholinesterase by copper - Mohd Khalizan Sabullah; Mohd Rosni Sulaiman; Mohd Yunus Abd Shukor; Nor Aripin Shamaan; Ariff Khalid; Siti Aqlima Ahmad (Technische Universitat Munchen, 2015)
The aim of this study is to determine the inhibitory effect of copper towards butyrylcholinesterase (BChE) activity. Using the Lineweaver-Burk plot, Puntius javanicus BChE activity was found to be noncompetitively inhibited by copper. The maximal velocities of untreated (control) BChE, 0.5 and 10 mg/L copper-treated BChE are 53.70, 31.81 and 14.30 Umg-1, respectively, while the biomolecular constant (Km) values of both tests shows no significant difference (p>0.05). The in vitro IC50 of copper ion to the BChE was found to be 0.0948 (0.0658 to 0.1691) mg/L. In vivo tests showed that in the presence of 0.1 mg/L copper, the BChE activity was slightly higher compared to the untreated control. Copper sulfate at 0.3 mg/L concentration showed no significant inhibition compared to control. However, the activity decreased with increasing copper concentrations of 0.5, 1.0 and 5.0 mg/L, with the remaining activity at 87.60, 84.60 and 73.00 %, respectively. This study suggests that BChE isolated from P. javanicus liver tissue is a potentially new source of biomarker for copper contamination.